Perancangan Sistem Informasi Penyewaan Alat Berat Berbasis Web Pada PT. Orang Kreatif Eksis Tangerang - Alifia, Aldi; Gunawan, Waliadi; Hidayanti, Nur (Jurnal Ilmiah Sains dan Teknologi, 2022)
Creative people exist is a company engaged in land transportation services, initially named UD. Creative. and change CV. Creative move forward together. Founded in early 1989 by Mr. Gobang Wijaya, he has more than twenty years of experience handling transportation and supply of finished goods or raw materials to Jabodetabek and Sumatra. Reservations and receipts of equipment rental orders are still running manually, in ordering equipment rental customers must come directly to the location, this results in limited time for customers to make tool rental orders and very small opportunities for companies to get orders outside working hours. In the midst of intense competition in the business world today, the Company is required to create opportunities to be superior to its competitors. In order to maintain trust and to increase the company's competitiveness, PT. Existing creative people must improve service to customers by fixing problems that often occur in implementation related to leasing at this time. The purpose of this study is to enable customers to place orders for tools remotely without being limited by distance and time. Facilitate companies in disseminating information about tool products offered to customers globally. This research was conducted using data collection methods (observations, interviews, literature studies). The design of the systems used in this research is using the Waterfall method. The designer of the heavy equipment rental information system uses the PHP and MySQL programming languages ​​as the database. The result of this research is an application of a web-based heavy equipment rental information system. With the rental information system is expected to provide convenience to PT. Creative people exist in carrying out their business activities related to leasing.